Real change begins inside: determinants and effects of organizational innovation, the case of the colombian agroindustry sector (2016)
Using data from the Colombian innovation survey for the period 2007-2008 (EDIT IV1), this paper analyzes determinants of organizational innovation and its effects on the propensity and capacity to innovate in products of Colombian agro industries. Factors explaining organizational innovation are analyzed with a logit model. In line with the existing literature and a sector analysis, four different groups of explanatory variables were included (one for the firm’s basic characteristics, one for variables approximating administrative capacities, one for innovation capacities which includes perception hampers and one for what we called “standardization” that includes process and product quality certificates). In addition using a propensity score matching (PSM) the paper analyzes the effect of organizational innovation on the firm´s innovation performance measured as innovation return of sales (ROS) and on the firm´s propensity to innovate in products. The results for both models are divided into small and medium-sized enterprises (SMEs) and large firms. The study findings primarily suggest that organizational innovation among the agroindustry varies depending on the firm’s characteristics, especially size. There is strong evidence of the importance of public funding to organizational innovation. This paper´s results suggest that firms that perform organizational innovations are more likely to increase their innovation ROS on products new to an international market and to increase their propensity to innovate at a radical level. The investigation provides evidence of complementary between organizational innovation and innovation in goods and services and remarks the importance of public policies aiming to increase the firm’s organizational capacities for innovation.